The effect of self-care education regarding high-risk behaviors of acquired immune deficiency syndrome and smoking on knowledge and attitude of adolescent girls: An experimental study to health promotion - Forogh Borandegi; Fatemeh Rahmanian; Zahra Yazdanpanahi; Azar Nematollahi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: The vulnerability of the youth to acquired immune deficiency syndrome (AIDS) and smoking is one of the most important public health issues around the world. Adequate knowledge about AIDS and smoking is a powerful tool for promoting positive attitudes and safe behaviors. OBJECTIVE: This study aimed to determine the effect of self-care education on AIDS and smoking on the level of adolescents' knowledge and health attitude. MATERIALS AND METHODS: This experimental study was conducted in the academic year of 2017-2018, and the participants were selected using randomized cluster sampling. These participants included 220 female students of the third grade of middle school in Isfahan (105 in the intervention group and 115 in the control group). Data were collected using a demographic questionnaire; a researcher-made questionnaire on knowledge about AIDS, knowledge about smoking, and attitudes toward smoking; and a standard questionnaire on students' attitude toward AIDS. After completing the pretest, the intervention group performed two training sessions and completed the posttest 1 month later. One month after completing the pretest, the control group completed the posttest and did not receive an intervention. Finally, the data were analyzed using descriptive statistics, statistical tests, and statistical software SPSS version 22. RESULTS: The results showed that despite the similarity between the two groups at the beginning of the study, after self-care education, the knowledge level of AIDS (P < 0.001) and attitude toward AIDS (P < 0.001) and the knowledge level of smoking (P < 0.001) and attitude toward smoking (P < 0.001) in the intervention group were significantly higher than the control group. In intragroup analysis, it was also observed that the difference between the scores before and after was only significant in the intervention group. CONCLUSION: It seems that education can promote the level of knowledge and attitude of adolescents toward AIDS.